The Urgency of Allignment Islamic Bank to Increasing the Outreach (Indonesia Evidence) - Nugroho, Lucky; Utami, Wiwik; Sukmadilaga, Citra; Fitrijanti, Tettet (International Journal of Economics and Financial Issues, 2017)
The outreach of Islamic Bank is critical to circulate out of maslahah (beneficiaries) to the community (Ummah) and the implementation of Sharia in totality (Kaffah). Nevertheless, Indonesia as the biggest Muslim in the world should facilitate the Muslim society to access their financial transaction needs based their Islamic law. The study aims to examine the outreach of Islamic Bank in Indonesia. The methodology in this literature review is qualitative that support with quantitative data. Three questions research is going to determine in this study are: (i) How the growth of Islamic Banks from 2008 to 2015? (ii) How many the clients that have sworn out by Islamic Banks? (iii) What is the link between maslahah and the Islamic Bank growth? We founded the outlet and business performance during 2008-2015 of Islamic Bank in Indonesia still behind from Conventional Bank thus to improve the backward we need interaction, integration and evolution process from all stakeholders. Due to achieve the increasing of outreach we also need the role of government in the political will that function to legitimate and enforce the alignment of Islamic Banks (Bank Syariah Mandiri, BNI Syariah, BTN Syariah and BRI Syariah) became one state own Islamic Bank which objective to create social well-being of the community. Keywords: Outreach, Maslahah, Kaffah, Allignment of Islamic Bank, State Own Islamic Bank, Social Well-being JEL Classifications: G02, G14, G2